Membrane-assisted enzymatic production of galactosyl-oligosaccharides from lactose in a continuous process - Czermak, Peter; Ebrahimi, M.; Grau, K.; Netz, S.; Sawatzki, G.; Pfromm, Peter H. (My University, 2004)
Functional foods such as oligosaccharides have attained significant acceptance in Japan and are attracting interest elsewhere. Beneficial physiological properties are attributed to oligosaccharides. Here, we describe the continuous production of oligosaccharides from a low-cost substrate (lactose) in a continuous membrane-assisted reactor (both polymeric and inorganic membranes were tested). Different enzymes, a number of feed concentrations, and different average residence times were investigated. The enzymes were used in their native form. Retention and recycling of the enzyme was successful, while the products together with some unreacted substrate and byproducts were removed as the ultrafiltration permeate. For the ultrafiltration, a steady-state flux of about 20 l/m2 hr was achieved. A maximum oligosaccharide concentration of over 40 %w/w was reached with an average residence time of 1 hr and a feed lactose concentration of 31 %w/w. Pilot scale experiments based on the laboratory tests are also reported.
Keywords: Ultrafiltration; Oligosaccharides; Enzymatic catalysis; Lactose